2019
DOI: 10.1016/j.respol.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

The interconnections of academic research and universities’ “third mission”: Evidence from the UK

Abstract: A considerable body of work acknowledges the importance and benefits of the universityindustry relationship for the economy and society, but also for increasing the revenue of universities themselves (known also as universities' "third mission"). However, questions have also been raised about the consequences of the university-industry relationship and its impact on their traditional role. This paper contributes to this debate by exploring whether and how being efficient in generating income from engagement ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 63 publications
0
28
0
Order By: Relevance
“…Chantler (2016) identifies three missions for HEIs: knowledge-transfer focused on education for employment and community service, knowledge creation through research and development and community engagement. We argue that the outbreak of the COVID-19 pandemic and its effects on the stakeholder systems that surround HEIs constituted a learning phase, which acted as a catalyst that accelerated changes in the governance of HEIs toward their third mission (Degl’Innocenti et al , 2019) and increased sustainability (Moon et al , 2018).…”
Section: Discussion: Stakeholder Reprioritizationmentioning
confidence: 99%
“…Chantler (2016) identifies three missions for HEIs: knowledge-transfer focused on education for employment and community service, knowledge creation through research and development and community engagement. We argue that the outbreak of the COVID-19 pandemic and its effects on the stakeholder systems that surround HEIs constituted a learning phase, which acted as a catalyst that accelerated changes in the governance of HEIs toward their third mission (Degl’Innocenti et al , 2019) and increased sustainability (Moon et al , 2018).…”
Section: Discussion: Stakeholder Reprioritizationmentioning
confidence: 99%
“…Successfully overcoming barriers to TT is key in ensuring longevity as well. The following are some of the micro issues that were specifically encountered in this case study and how addressing them led to the successful co-creation of process and fulfilling the requirement of needing incentive to all parties involved to create successful TT's (Degl'Innocenti et al , 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Academic quality and quality of research work building trust and reliance on external entities play a significant role in university-industry collaboration. Individuals who produce high-quality research could attract more external collaboration and rise more external funds (Degl et al, 2019). It was found that about 10% of new products and processes introduced by firms would not simply be possible without scientific research studies carried out by academics (Mansfield, 1991).…”
Section: Review Of Literaturementioning
confidence: 99%